Byzantium: A Very Short Introduction - Sarris, Peter (New York Oxford University Press, 2015)
From the fourth to the fifteenth century AD the Byzantine Empire flourished as a powerful economic, cultural, and military force, whose influence stretched from Spain to Egypt. Peter Sarris explores the fusion of Greek and Roman civilization at the heart of the Byzantine Empire, and charts its struggle for survival against external challenges.
Includes Index and Illustrations.
Keywords: Byzantine Empire